O uso de ambiente colaborativo digital como ferramenta de produção da escrita na escola - Maciel, Gerson Luís (2016)
Traditional studies of Portuguese language are focused on grammar rules, also known as prescriptive. But there are some text studies and decades of discourse brought new way to treat the text, which has been occurring since the 1980s Moreover, with the advent of information and communication technologies, it is often the production and circulation of texts hybrids, or produced from many semiosis. In literacy events of this nature, the statements that are part of the lives of adolescents and young people are thus produced and circulate in technologies that combine sound, image, movement and words in a multi-way relationship. In this context, treating the text considering only the verbal aspect is to ignore the extent of any practical language usages in which adolescents and young people are included. Therefore, to meet a teaching project whose goal is to understand the writing production in more authentic situations, it is necessary to consider the relationship between teens, technology and virtual environment. The emergence and popularization of hybrid texts in multiple contexts, makes it even more complex craft teacher in work, school, text and context. And it is this complexity that motivated the objectives of this study and therefore the formulation of the question: - What brings gains for the production written at school, the exploitation of activities in digital collaborative environment? This work is a qualitative-interpretative and ethnographic research from documents located in the area of Applied Linguistics and comprises the production of gender "opinion piece" production that performed in five groups of students about in digital tool - Google Drive - connected to the internet. The records generated by this tool form the analysis of material from which the data in this study were generated. The overall objective was to conclude that earnings exploitation of literacy practices in collaborative virtual environment can be obtained for the production of writing in school. As for the specific objectives are to analyze how interactions (speeches and dialogues) between students build a knowledge related to the production of written texts and how the digital context affects the configuration of the proposed speech. The analysis found that the displacement of predominantly verbal text focus to set multisemiotic brought some gains for writing production, for example, exploring the relationship between verbal and image, using link and hyperlink to establish a relationship Intertextual and increase the informative and argumentative level of the text. The articulation of different semiosis, in a multiplicity of meanings, extends the ideas contained in the final text of groups produsuários students. It was also detected that the use, by itself, does not bring new technology guarantees that the operation of large amounts of light information to produce a better quality writing point of view of integration skills.